Prevention of methicillin-resistant Staphylococcus aureus (MRSA) infection by pre-admission screening : the cost-effectiveness, practical and ethical issues for implementation in Malaysia - Bostamam, Suazlini; Azman, Putri Arsyadiana; A. Rahman, Nor Azlina; Mohamad Zin, Noraziah; Mohammad, Mardhiah; Baba, Mohd Shukri (2016)
MRSA is a multi-resistant S.aureus bacteria which can colonize or infect humans either in the community or hospitals. Being increasingly common as a cause of nosocomial infection, active actions need to be taken to control and prevent this costly and serious infection which can lead to mortality. One of the control measures which can be taken in the hospital setting is by screening patients for colonization of MRSA upon admission so that active precaution and direct treatment can be given to the positive patients to prevent the transmission of the infection in the ward. The objectives of this study is to review the cost and effectiveness of different methods of pre-admission MRSA screening by doing a comprehensive systematic review of literatures and to explore the opinion, experience and perceptions of the relevant stakeholders such as the hospital administrators, specialists and doctors, nurses, laboratory personnels, patients and relatives with respect to the cost, practical and ethical issues concerning the screening by doing in-depth interview and focus group discussion. Qualitative study was carried out to get the information from the stakeholders through in-depth interview and focus group discussion from a government hospital (Hospital Tengku Ampuan Afzan, Kuantan) and a teaching hospital (University Kebangsaan Malaysia Medical Centre). The stakeholders’ opinion was sought in order to find possible solutions to probable problems that may arise from the implementation of the MRSA screening. Manual note taking and audio-visual kit was used during data collection to facilitate the transcribing process and data analysis which was done using Nvivo software. It was found out that majority of the respondents did not agree for pre-admission screening for MRSA to be carried out to all patients because of the impracticalities in terms of cost and man-power. However, it could be possible and more cost-effective is an effective and cheap rapid test kit is available for the screening.